The profile of digital exclusion in Brazilian society (Journal of Information Systems and Technology Management, 2005)
The digital exclusion comes gaining prominence in the last years. The attentions are converging to this subject that is already seen as a cause and consequence of exclusion in our society. Brazil has a lot of inequalities that creates a request for politics of transference and income generation. However, it is not enough become the ways available, it is important show to people how the technologies can contribute for their tasks and activities, bringing knowledge and opportunities. This work, based on bibliographical, reflexive and qualitative researches, approaches the aspects that are usually associated with digital exclusion, as the social exclusion, the knowledge society, the e-gov and contemporary economy, among others, and the factors that need to be taken in consideration to prepare combat politics for digital exclusion. As a result of this reflection, its possible to identify some of the real consequences and the meaning of the digital exclusion in the Brazilian society. The motal of this work was the observation of impacts that information technology over work and the Brazilian citizens' life.